Issues, obstacles and outlook for the Copenhagen International Climate Change Negotiation - Walsh, Sean (The Centre for International Governance Innovation WaterlooCA, 2009)
Sets out some of the critical issues and obstacles standing in the path of a successful conclusion in Copenhagen.